Strategi Pemasaran Syariah Dan Waiting List Terhadap Keputusan Nasabah Menggunakan Produk Tabungan Haji Pada PT BRISyariah KCP Genteng Kabupaten Banyuwangi - Nur Anim Jauhariyah; Ahmad Munawar; Mahmudah Mahmudah (JOURNAL OF SHARIA ECONOMICS, 2020)
The purpose of this study is 1) to find out and analyze the influence of sharia marketing strategy (X1) on customer decisions (Y) using Hajj savings products in BRISyariah KCP Genteng Banyuwangi district; 2) to find out and analyze the influence of the waiting list (X2) on the customer's decision (Y) to use the Hajj savings product at BRISyariah KCP Genteng Banyuwangi district; 3) to find out and analyze the influence of sharia marketing strategy (X1) and waiting list (X2) simultaneously on the customer's decision (Y) to use Hajj savings products in BRISyariah KCP Genteng Banyuwangi district. The research method is quantitative with the type of survey research. Research Results 1) there is a significant influence of sharia marketing strategy (X1) on the customer's decision (Y) to use the Hajj savings product at BRISyariah KCP Genteng Banyuwangi district; 2) there is no significant influence of the waiting list (X2) on the customer's decision (Y) to use the Hajj savings product at BRISyariah KCP Genteng Banyuwangi district; 3) there is a significant influence of sharia marketing strategy (X1) and waiting list (X2) simultaneously on the customer's decision (Y) to use Hajj savings products in BRISyariah KCP Genteng Banyuwangi district. Marketing and waiting list strategies are not dominant in influencing prospective customers to use Hajj savings products. The influence exerted was only 41%. Keywords: Sharia Marketing Strategy, Waiting List, and Customer Decisions